Vitamin D3-PEGylated hexosomes for gemcitabine and thymoquinone co-delivery: Unraveling the physicochemical characteristics, biocompatibility, and cytotoxicity against breast cancer cells - Loo, Yan Shan; Yusoh, Nur Aininie; Zahid, N. Idayu; Madheswaran, Thiagarajan; Ikeno, Shinya; Nurdin, Armania; Salim, Norazlinaliza; Lim, Hong Ngee; Mat Azmi, Intan Diana (Editions de Sante, 2025)
An integration between co-delivery and the targeting ability of nanoparticles confers an important clinical implication in breast cancer treatment, as the progression, recurrence, and development of resistance towards standard therapy are associated with a crosstalk of aberrant signaling pathways. In this study, lipid-based nanoparticles structurally defined by the presence of an inverse hexagonal phase with aqueous channels within, i.e., hexosomes, were investigated for gemcitabine and thymoquinone (Gem-TQ) co-delivery and surface functionalization with vitamin D3-methoxypoly(ethylene glycol)2000 (VD-PEG). These hexosomes were prepared using soy phosphatidylcholine (SPC) and an emulsifier, citric acid esters of monoglycerides (citrem). VD-PEG/SPC/citrem/Gem-TQ hexosomes demonstrated mean hydrodynamic particle size of 336.5 ± 5.4 nm and entrapment efficiency of 97.7 ± 0.1 % (Gem) and 99.0 ± 0.1 % (TQ) at the compositional ratio of 2.5:2.5:0.1 wt% (SPC:citrem:VD-PEG) and co-loading at 2:9 μM Gem-TQ. Moreover, the half-maximal lethal dose (LD50) of VD-PEG/SPC/citrem/Gem-TQ determined in zebrafish (Danio rerio) embryos at Gem:TQ concentration of 4.6:20.8 μM was reduced by 1.3-fold compared to LD50 of Gem-TQ (non-encapsulated) solution. In addition, the inhibitory concentrations (IC50) following 24 h treatment using VD-PEG/SPC/citrem/Gem-TQ hexosomes were 33.4 ± 8.0 μM and 23.8 ± 2.9 μM against MCF7 and T-47D hormone receptor-positive luminal breast cancer cells, respectively. VD-PEG/SPC/citrem/Gem-TQ hexosomes containing methylene blue (MB) as the molecular fluorescent probe demonstrated higher cellular uptake in T-47D compared to MCF7 cells, therefore, the use of VD-PEG for the fabrication of lyotropic liquid crystalline nanoassemblies can be further investigated for its therapeutic potency and targeting mechanisms.